Successful administration of BI 695501, an adalimumab biosimilar, using an autoinjector (AI): results from a Phase II open-label clinical study (VOLTAIRE®-RL). (3rd June 2018) - Cohen, Stanley; Klimiuk, Piotr A.; Krahnke, Tillmann; Assudani, Deepak
ABSTRACT: Background : This study examined the patient handling experience and self-injection success of patients with rheumatoid arthritis (RA) administering BI 695501 using an AI. Methods : This Phase II, 7-week, open-label, interventional study (NCT02636907) included adult patients with moderately to severely active RA not adequately controlled by DMARDs, with no experience of self-injecting with AI/pen. Patients self-injected BI 695501 via AI every 2 weeks in the AI Assessment Period (AAP). Training was given on first injection; AI handling events were recorded. Percentage of self-injection success was the primary end point. Patients could enter a 42-week pre-filled syringe (PFS) safety extension. Results : The AAP was completed by 73/77 patients. In total, 216/218 (99.1%) self-injections on Days 15, 29, and 43, were successful. Nine (11.7%) patients had drug-related adverse events (AEs). Two patients reported four serious AEs (SAEs), none drug-related. Overall (in the AAP and PFS extension), 28 (36.4%) patients had drug-related AEs; nine patients had SAEs, one was considered drug-related. Five (6.5%) patients reported injection-site reactions in the AAP; 13 (18.1%) in the PFS extension. Conclusions : After training, almost all patients were successfully able to self-administer BI 695501 using an AI. BI 695501 via AI (and via PFS in the extension) was well tolerated. Clinical Trial Registration: NCT02636907